2002
DOI: 10.1128/mcb.22.13.4463-4476.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Domain in the G1 Cyclin Cln2 Sufficient To Switch Degradation of Sic1 from the E3 Ubiquitin Ligase SCFCdc4 to SCFGrr1

Abstract: Degradation of Saccharomyces cerevisiae G(1) cyclins Cln1 and Cln2 is mediated by the ubiquitin-proteasome pathway and involves the SCF E3 ubiquitin-ligase complex containing the F-box protein Grr1 (SCF(Grr1)). Here we identify the domain of Cln2 that confers instability and describe the signals in Cln2 that result in binding to Grr1 and rapid degradation. We demonstrate that mutants of Cln2 that lack a cluster of four Cdc28 consensus phosphorylation sites are highly stabilized and fail to interact with Grr1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 53 publications
2
52
0
Order By: Relevance
“…However, despite the fact that deletion of its PEST sequence stabilizes Ho (6), we found that this does not abolish binding to Ufo1. This suggests that there are other phosphorylated residues on Ho that participate in binding to Ufo1 and is consistent with the finding that PEST sequences alone, when fused to a heterologous protein, are not enough to destabilize it (12,43). Indeed our data show that Ho with a single mutation in its PEST sequence, threonine 225 to alanine, although resistant to degradation, still binds Ufo1 with an affinity not visibly different from that shown by wild type Ho.…”
Section: Discussionsupporting
confidence: 78%
“…However, despite the fact that deletion of its PEST sequence stabilizes Ho (6), we found that this does not abolish binding to Ufo1. This suggests that there are other phosphorylated residues on Ho that participate in binding to Ufo1 and is consistent with the finding that PEST sequences alone, when fused to a heterologous protein, are not enough to destabilize it (12,43). Indeed our data show that Ho with a single mutation in its PEST sequence, threonine 225 to alanine, although resistant to degradation, still binds Ufo1 with an affinity not visibly different from that shown by wild type Ho.…”
Section: Discussionsupporting
confidence: 78%
“…The PEST sequence has been reported to be located in some proteins with fast turnover rates and be essential for the interaction between SCF complex and target proteins, which consequently leads to ubiquitination/26S proteasome-mediated degradation (Kiernan et al, 2001;Berset et al, 2002;Blondel et al, 2005;Pal et al, 2007). Human SAMDC was reported to have a short half-life and is regulated at multiple levels, such as the transcriptional, translational, and posttranslational levels (Shantz et al, 1992;Stanley et al, 1994;Hanfrey et al, 2003;Yerlikaya and Stanley, 2004).…”
Section: Bsctv C2 Interacts With Arabidopsis Samdc1mentioning
confidence: 99%
“…SAMDC is synthesized as an inactive proenzyme that generates two subunits, termed a and b, by an autocatalytic cleavage reaction. SAMDCs in many organisms are highly conserved, sharing a defined autocleavage recognition site and a PEST region enriched in Pro (P), Glu (E), Ser (S), and Thr (T) that is correlated with the protein's rapid turnover (Salama et al, 1994;Rechsteiner and Rogers, 1996;Berset et al, 2002;Blondel et al, 2005;Pal et al, 2007). SAMDC is expressed throughout the cell, and its expression is regulated at multiple levels, such as the transcriptional, translational, and posttranslational levels (Shantz et al, 1992;Stanley et al, 1994;Hanfrey et al, 2003;Yerlikaya and Stanley, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Note that the low endogenous expression of Doa4 is difficult to detect. (D) Western blot analysis of extracts prepared from pep4⌬ doa4 C571S SNA3-HA cells (MMY64) that had been transformed either with empty low-copy vector (pRS414) or pRS414 encoding Myc-Ub (pUB223; Berset et al, 2002) and incubated with 250 M CuSO 4 to induce overexpression of Myc-Ub. Unmodified full-length Sna3-HA migrates at ϳ25 kDa.…”
Section: Rsp5 Mediates Polyubiquitination Of Sna3mentioning
confidence: 99%